Oscilloscope training system - Yuen, Wei Liong. (2011)
Students whom are pursuing a degree in computer engineering are required to operate the oscilloscope for their laboratory sessions throughout their course of study. As the oscilloscope is a specialized kind of testing equipment, most students faced difficulties in operating the oscilloscope. Hence, it would be beneficial to have a platform for them to learn about the fundamentals and operating information of the oscilloscope.